Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.3389/fpsyg.2017.01786
|View full text |Cite
|
Sign up to set email alerts
|

Brain Functional Plasticity Driven by Career Experience: A Resting-State fMRI Study of the Seafarer

Abstract: The functional connectome derived from BOLD resting-state functional magnetic resonance imaging data represents meaningful functional organizations and a shift between distinct cognitive states. However, the body of knowledge on how the long-term career experience affects the brain’s functional plasticity is still very limited. In this study, we used a dynamic functional connectome characterization (DBFCC) model with the automatic target generation process K-Means clustering to explore the functional reorganiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 64 publications
3
25
0
Order By: Relevance
“…The specific scan parameters were as follows: GE 3.0 T using a gradient echo EPI, a total of 36 slices covering the whole‐brain area, 160 time points, TR (time of repetition) = 2 s, matrix size = 64 × 64, in‐plane resolution = 3.75 mm × 3.75 mm, and slice thickness = 4 mm. This dataset was also reported in our previous research (Wang et al, ).…”
Section: Methodssupporting
confidence: 82%
See 4 more Smart Citations
“…The specific scan parameters were as follows: GE 3.0 T using a gradient echo EPI, a total of 36 slices covering the whole‐brain area, 160 time points, TR (time of repetition) = 2 s, matrix size = 64 × 64, in‐plane resolution = 3.75 mm × 3.75 mm, and slice thickness = 4 mm. This dataset was also reported in our previous research (Wang et al, ).…”
Section: Methodssupporting
confidence: 82%
“…The superior temporal gyrus is an essential structure involved in auditory processing, as well as the function of hearing, speech, language (Bigler et al, ; Howard et al, ; Tang, Hamilton, & Chang, ), and integration of multimodal sensory input (Barraclough, Xiao, Baker, Oram, & Perrett, ). Thus, we inferred that the increase in brain entropy in the superior temporal gyrus of the seafarer was possibly due to the marine working environment, which has continuous machine noise, the monotonous loud sound of surf, and the less communicative community of single‐sex colleagues (Wang, ; Wang et al, ). Furthermore, previous studies have demonstrated that the orbito‐frontal gyrus plays a key role in the regulation of the peripheral physiological response during emotional experiences (Barbas, ; Barrett, Mesquita, Ochsner, & Gross, ; Bechara, Damasio, & Damasio, ; Bishop, Duncan, Brett, & Lawrence, ; Kim, Gee, Loucks, Davis, & Whalen, ; Meyers, Berman, Scheibel, & Hayman, ; Ohira et al, ) and in the planning behaviors associated with reward and punishment (Bechara, Damasio, Damasio, & Anderson, ; Wei et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations